Performance of lateritic soil stabilized with combination of bone and palm bunch ash for sustainable building applications. Issue 1 (1st January 2021) - Obianyo, Ifeyinwa Ijeoma; Mahamat, Assia Aboubakar; Anosike-Francis, Esther Nneka; Stanislas, Tido Tiwa; Geng, Yang; Onyelowe, Kennedy Chibuzor; Odusanya, Shola; Onwualu, Azikiwe Peter; Soboyejo, Alfred B. O.
Abstract: Various research works have been carried out on cement and lime stabilization of lateritic soil. The production of cement is too expensive and environmentally unfriendly due to the required huge embodied energy as well as the environmental pollution resulting in ozone layer depletion. In order to minimize these shortcomings, researchers are exploring a sustainable alternative to cement. There is limited scholarly work done on the use of a combination of agro-waste ashes for the stabilization of lateritic soil. This study is aimed at examining the performance of lateritic soil stabilized with a combination of bone ash (BA) and palm bunch ash (PBA) for sustainable building applications. Different cube sizes (50 mm 3, 70 mm 3, and 100 mm 3 ) were used to produce lateritic bricks of different matrices which were used to obtain the compressive strength test results. Addition of a minimal percentage of BA (2%) and PBA (2%) improved the compressive strength of lateritic bricks by 129% compared to the natural lateritic soil. Brick specimen produced with the smallest mould size (2500 mm 2 ) gave higher compressive strength compared to larger mould size. The findings of this study confirm the potential of using lateritic soil stabilized with a minimal percentage of BA (2%) and PBA (2%) for sustainable building applications.